Study the Effect New Numerical and Analytical Solutions For Heat Irreversibility of Thermal Radiation and Ohmic Heating on Williamson Fluid - Khlefha, Ahmed R; Jasim, Abeer M (Iraqi Journal of Science, 2025)
In this paper, the numerical and analytical treatment for the heat irreversibility of thermal radiation and Ohmic heating on Williamson fluid problem is investigated with various physical parameters and the new initial conditions which poses arbitrary constants. The governing equations are transformed into dimensionless formulas, the ordinary differential equations obtained are then solved using the BVP4c and the differential transform method (DTM) . The heat irreversibility analysis is achieved by substituting the obtained results into entropy generation and Bejan number expressions. The results of numerical and analytical solutions for various parameters are compared. Fluid motion is reduced by the increasing values of thermal radiation parameter, the magnetic parameter and Reynolds number. In addition, every flow parameter investigated increases fluid temperature exception thermal radiation parameter. Entropy generation is also improved at the upper wall of the channel.